P202 Dietary management of chylothorax in congenital heart disease. (June 2019) - Tuohy, Michelle; Shine, Anne Marie; Gentles, Emma; McGuinness, Jonathan
Abstract : Background: Chylothorax can be defined as the presence of chyle in the pleural cavity resulting from impeded flow in the thoracic duct. In childhood chylothorax is a potentially challenging postoperative complication of cardiothoracic surgery. It may have a detrimental effect on a patient's nutritional and immunological state. Conservative treatment includes the use of a minimal LCT diet or total parenteral nutrition. Aim: The aim of this audit was to determine the incidence of chylothorax and dietary management post congenital heart surgery in OLCHC from January 2017 – December 2018. Method: The number of cardiac surgeries was provided by the cardiac data manager for OLCHC. The number of patients diagnosed with postoperative chylothorax and dietary management data was collated from medical records, product information system and dietetic notes. Results: In 2017, 32 patients received dietary treatment out of a total of 395 patients (8%) post cardiac surgery in OLCHC. The number of Trisomy 21 cases were 11 out of the total 32, 34%. In 2018, 24 patients received dietary treatment out of a total 382 patients (6%) post cardiac surgery in OLCHC. The number of Trisomy 21 cases were 11 out of the total 24, 46%. 21 infants were receiving breast milk pre surgery, 10(48%) returned to breast milk post-surgery of which 9 were breastfeeding. In 2017 and 2018 respectively, only 3 and 5 patients required parenteral nutrition. The majority of patients were managed on oral or enteral nutrition. Conclusion: The results show a reduction of 2% in dietary management of chylothorax in OLCHC in 2018 compared to 2017. Incidence rates reported relate to those that received dietary management, the audit also provides an analysis on the actual incidence rates including those not treated. The incidence of chylothorax in OLCHC is high in comparison to other countries. However, complexity of surgery's and the population group may not be comparable. Of note a high percentage of chylothorax cases had a diagnosis of T21, up to 46% in 2018. Further research to understand the mechanisms of chylothorax in T21 is warranted. Dietary management of chylothorax appears to effect maintenance of breast milk feeding. Of concern 52% of infants did not return to breast milk post management of chylothorax. There is ongoing consultation with surgeons and the cardiology team to review OLCHC's protocol aiming to standardise care.